Tailoring Recognition to Fit your Employees’ Needs - Matthew Benge (EDIS)
Employee recognition plays a key role in the success and continuity of productivity, efficiency, and organizational change. This 2-page document discusses employee recognition practices that you can implement in your workplace. Written by Matt Benge and published by the UF/IFAS Department of Agricultural Education and Communication, February 2018. http://edis.ifas.ufl.edu/wc298